2022
DOI: 10.3389/fpsyg.2022.880234
|View full text |Cite
|
Sign up to set email alerts
|

The Role of EFL Teachers’ Emotioncy in Preventing Students’ Boredom and Pessimism

Abstract: It is widely approved that emotions play a critical role in language education. This inspires EFL teachers to establish a classroom oriented toward students’ emotions and senses involved in the teaching/learning processes. Such an emotioncy-based pedagogy can bring about various positive outcomes in second/foreign language education. In tune with this, the present study briefly reviews the definitions, models, roots, and potentials of emotioncy in stopping student’ boredom and pessimism. Moreover, it makes som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…This is indicated by low self-confidence (ST4, ST9, ST2), pessimistic attitude when encountering challenging aspects of the target language (ST6), anxiety of meeting expectations in using the TL (ST7 and ST8), and fear of judgement when using the TL (ST4 and ST9). When these factors are present, second language learners become apprehensive towards the target language, inhibiting them from equipping the necessary knowledge and skills to become competent in the target language (Zhang, 2022). In fact, a study done by Bao and Liu (2021) showed that regardless of how much exposure to meaningful and comprehensive linguistic inputs these students receive, for as long as the affective filter is up, second language learning will be repressed.…”
Section: High Affective Filtermentioning
confidence: 99%
“…This is indicated by low self-confidence (ST4, ST9, ST2), pessimistic attitude when encountering challenging aspects of the target language (ST6), anxiety of meeting expectations in using the TL (ST7 and ST8), and fear of judgement when using the TL (ST4 and ST9). When these factors are present, second language learners become apprehensive towards the target language, inhibiting them from equipping the necessary knowledge and skills to become competent in the target language (Zhang, 2022). In fact, a study done by Bao and Liu (2021) showed that regardless of how much exposure to meaningful and comprehensive linguistic inputs these students receive, for as long as the affective filter is up, second language learning will be repressed.…”
Section: High Affective Filtermentioning
confidence: 99%
“…The significant impact of online technologies on the future of language instruction is clearly seen in the swift transformation of conventional educational methods. With the continuous advancement of technology and the rising sophistication of online tools, the traditional classroom is being enhanced, if not replaced, by digital alternatives (Aavakare, 2019;Haleem et al, 2022;Lo, 2023;Zhang, 2023;Z. Zhou, 2018).…”
Section: Introductionmentioning
confidence: 99%